Fungsi Marketing Public Relations Shopeefood dalam Membangun Brand Awareness pada Masa Pandemi Covid-19 - Yehezkiel Yehezkiel; H.H Daniel Tamburian (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
In an era that is developing rapidly as it is today, humans live in an era that is convenient. Many creations of technology that can facilitate human needs. This is due to the rapid development of digitalization. Similar to the food delivery service application from Singapore, Shopeefood which has expanded to Indonesia in the early 2020. The purpose of this research is to find out how Shopeefood's Marketing Public Relations function in building Brand Awareness during the Covid-19 pandemic and its obstacles. This study uses a qualitative approach with data collection methods conducted by interviewing key informants and informants. The theory used is Public Relations, Brand Awareness, Marketing Public Relations. Researchers conducted interviews with 3 resource persons related to Shopeefood's Marketing Public Relations. The data analysis technique used is data reduction, data presentation and conclusion drawing. The results of the data analysis show that Marketing Public Relations has an important role in building Shopeefood Brand Awareness during the Covid-19 pandemic.Di era yang berkembang pesat seperti sekarang ini, manusia hidup di zaman yang serba mudah. Banyak terciptanya teknologi yang dapat memudahkan kebutuhan manusia. Hal ini terjadi karena perkembangan digitalisasi yang sedang berkembang dengan pesat. Sama halnya dengan aplikasi jasa layanan antar makanan asal Singapura, Shopeefood yang telah berkespansi hingga ke Indonesia pada awal tahun 2020. Tujuan penelitian ini adalah untuk mengetahui bagaimana fungsi Marketing Public Relations Shopeefood dalam membangun Brand Awareness pada masa pandemic Covid-19 serta hambatannya. Penelitian ini menggunakan pendekatan kualitatif dengan metode pengumpulan data yang dilakukan dengan wawancara kepada Key informan dan Informan. Teori yang digunakan ialah Public Relations, Brand Awareness, Marketing Public Relations. Peneliti mengadakan wawancara kepada 3 Narasumber yang terkait dengan Marketing Public Relations Shopeefood. Teknik Analisis data yang digunakan adalah reduksi data, penyajian data dan penarikan kesimpulan. Hasil dari analisis data menunjukkan Marketing Public Relations memiliki peran penting dalam membangun Brand Awareness Shopeefood pada masa pandemic Covid-19.